Michael Field's Paratextual Poetics: Portraying a Protomodernist Sappho - Cantillo Lucuara, Mayron Estefan (Complutense Journal of English Studies, 2023)
This article offers an innovative perspective on Katharine Bradley and Edith Cooper’s Long Ago (1889), their Sapphic volume of verse published under the Michael Field pseudonym. Rather than propounding new interpretations of the lyrics in the collection, I focus on its paratextual apparatus –from the cover and the frontispiece to the endnotes or appendix– with the aim of unveiling a significant aspect that has been overlooked by most critics: the fact that, in its rich paratextuality, Long Ago possesses an effective illocutionary force that seduces the reader, pre-establishes a clear interpretive framework, and activates an innovative dialogue with the past. This paratextual dialogue, I conclude, results in a protomodernist reworking of Sappho as an enigmatic, unstable, and radically open (para)textual figure –one that is always ready to be made new.